2023
DOI: 10.1242/dev.201606
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation dynamic in male rat germ cells during gametogenesis

Abstract: In mammals, a near complete resetting of DNA methylation (DNAme) is observed during germline establishment. This wave of epigenetic reprogramming is sensitive to the environment which could impair the establishment of an optimal state of the gametes’ epigenome, hence proper embryo development. Yet, we lack a comprehensive understanding of DNAme dynamics during spermatogenesis, especially in rats, the model of choice for toxicological studies. Using a combination of cell sorting and DNA methyl-seq capture, we g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…These regions correspond to genes specifically expressed by spermatids. Our hypothesis is further corroborated by analogous results in rodents, which demonstrate that the spermatid methylome undergoes differential methylation during spermiogenesis and is enriched for regulatory binding sites when compared to spermatogonial stem cells (Kubo et al , 2015; El Omri-Charai et al , 2023).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These regions correspond to genes specifically expressed by spermatids. Our hypothesis is further corroborated by analogous results in rodents, which demonstrate that the spermatid methylome undergoes differential methylation during spermiogenesis and is enriched for regulatory binding sites when compared to spermatogonial stem cells (Kubo et al , 2015; El Omri-Charai et al , 2023).…”
Section: Discussionsupporting
confidence: 83%
“…The establishment of the germ cell methylome extends beyond prenatal development (Oakes et al , 2007; Langenstroth-Röwer et al , 2017; Di Persio et al , 2021a; El Omri-Charai et al , 2023; Huang et al , 2023). In this study, we used whole methylome sequencing of germ cells to identify changes in DNA methylation occurring during human spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global methylation drop of around 12-13% occurs in preleptotene spermatocytes and methylation is gradually reestablished during leptotene-pachytene stages so that the final DNA methylation patterns are obtained by the end of pachytene spermatocyte stage (Gaysinskaya et al, 2018 ;Loukinov et al, 2002 ;Oakes et al, 2007 ). A recent rat study identified the transition from elongating spermatids to late spermatids as another stage associated with changes in methylation of more than 5,000 DNA regions (Omri-Charai et al, 2023 ). After fertilization, most parental-specific epigenetic marks of gametes undergo reprogramming to establish totipotency in the developing embryo.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that the establishment of the male germ cell methylome is not restricted to embryonic development but continues in adulthood during spermatogenesis. 1 , 2 , 3 , 4 , 5 Especially in the early phases of meiosis, when replication and recombination occur, the genome is hypomethylated. This event is highly conserved between mouse and human and has been hypothesized to result from a delay in DNA methylation maintenance.…”
Section: Introductionmentioning
confidence: 99%